High-brightness anterograde transneuronal HSV1 H129 tracer modified using a Trojan horse-like strategy - Peng Su; Min Ying; Zengpeng Han; Jinjin Xia; Sen Jin; Yingli Li; Huadong Wang; Fuqiang Xu (Molecular Brain, 2020)
Abstract Neurotropic viral transsynaptic tracing is an increasingly powerful technique for dissecting the structure and function of neural circuits. Herpes simplex virus type 1 strain H129 has been widely used as an anterograde tracer. However, HSV tracers still have several shortcomings, including high toxicity, low sensitivity and non-specific retrograde labeling. Here, we aimed to construct high-brightness HSV anterograde tracers by increasing the expression of exogenous genes carried by H129 viruses. Using a Trojan horse-like strategy, a HSV/AAV (adeno-associated virus) chimaera termed H8 was generated to enhance the expression of a fluorescent marker. In vitro and in vivo assays showed that the exogenous gene was efficiently replicated and amplified by the synergism of the HSV vector and introduced AAV replication system. H8 reporting fluorescence was brighter than that of currently available H129 tracers, and H8 could be used for fast and effective anterograde tracing without additional immunostaining. These results indicated that foreign gene expression in HSV tracers could be enhanced by integrating HSV with AAV replication system. This approach may be useful as a general enhanced expression strategy for HSV-based tracing tools or gene delivery vectors.